Factors related to fatigue among workers in life saving equipment manufacturing factory, Laemchabang Industrial Estate Chonburi Province - พันหา ศิริภาพร; ล้อมพงศ์ ศรีรัตน์ (Disease Control Journal, 2014)
This Study was cross-sectional descriptive research. The objective was to determine factors related to fatigue among workers in life saving equipment manufacturing factory Laemchabang Industrial Estate Chonburi Province. The study was conducted doring, May-June 2013. There were 222 informal sector workers interviewed. The interview consisted of (1) General information (2) Working Environmental (3) Health information (4) Knowledge of fatigue and, (5) modified standardized Nordic questionnaire in Thai version. Statistic were frequency, percentage, standard deviation and Chi-square. The result found that 55.9% of workers was women and 55.0% age between 30-39 years. 52.3% was married. 38.7% was High school education. 68.5% was work experience between 1-5 years, average work experience was 3.51 year. 95.9% was over time, for health information. 76.1 % didn’t have underlying disease. 88.7% was never sick to admission with musculoskeletal disorder. 98.6% have been fatigue after work, 57.1% was fatigue someday, method to relieve fatigue was 46.4% press, massage or massage with hot press. 57.7% was relaxed and adjust in working to relive fatigue and 96.8% knew about using tool to move material. The last 7-day period was found in the following three anatomical area: low back, calf and wrist. The last 3-month period was found in the following three anatomical area: low back, wrist and hip. The last 12-month period was found in the following three anatomical area: low back, foot and calf, when analyzing factors related which fatigue, those were not statistically significantly.